A cross-country study of service productivity. Issue 5 (25th April 2016) - Sekhon, Harjit; Yalley, Andrews Agya; Roy, Sanjit Kumar; Shergill, Gurvinder Singh
ABSTRACT: This study empirically examines service productivity and complements prior studies by framing service productivity as consisting of a number of key constituents. Adopting a bottom-up approach we present an integrative model proposing that resource commitment is the core from which employee readiness and customer readiness flow. These inform service productivity, which, in turn, informs job security. Our empirical examination reveals that service productivity has an impact on perceptions of job security, while resource commitment has the greatest impact on both employee readiness and customer readiness. In developing our integrative model we provide a framework that other researchers can apply, particularly where the service is highly intangible or in the public sector where service providers are being increasingly challenged to demonstrate value for money.